How Voters Respond to Presidential Assaults on Checks and Balances: Evidence from a Survey Experiment in Turkey - Aytuğ Şaşmaz; Alper H. Yagci; Daniel Ziblatt (Comparative Political Studies, 2022)
Why do voters support executive aggrandizement? One possible answer is that they do so because they think this will ease their preferred leader's hand in putting their partisan vision into action, provided that the leader will continue winning elections. We study this phenomenon through a survey experiment in Turkey, by manipulating voters' perceptions about the potential results of the first presidential election after a constitutional referendum of executive aggrandizement. We find that voters from both sides display what we call “elastic support” for executive aggrandizement; that is, they change previously revealed constitutional preferences in response to varying winning chances. This elasticity increases not only when citizens feel greater social distance to perceived political “others” (i.e., affective polarization) but also when voters are concerned about economic management in a potential post-incumbent era. Our findings contribute to the literature on how polarization and economic anxiety contribute to executive aggrandizement and democratic backsliding.
https://doi.org/10.7910/DVN/IGVQIT
Keywords: 320; democratic backsliding; executive aggrandizement; referenda; voter behavior; polarization